PENGARUH FDR DAN NPF TERHADAP ROA BANK UMUM SYARIAH INDONESIA 2017-2020 - Thoyibatun Nisa; Lella Anita; Carmidah Carmidah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
The high and low FDR and NPF is a risk to profitability. If he FDR is lower then the bank's effectiveness in channeling credit is lower, while the higher NPF will result in a decreased ROA and the company's profit income will decrease. This study aims to determine the effect of FDR and NPF on ROA at Islamic Commercial Banks in Indonesia for the 2017-2020 period. This research is a quantitative research with secondary data of 14 Islamic Commercial Banks in Indonesia. The data analysis technique in this study used the SPSS program. V.22 with descriptive analysis method, classical assumption test and hypothesis test to see and assess performance based on ROA, FDR, and NPF. The results of this study indicate that FDR and NPF partially have no significant effect on ROA. FDR and NPF have an effect of 57.2% on ROA, while 42.8%are influenced by other variables.